2017
DOI: 10.1093/ajcp/aqx018
|View full text |Cite
|
Sign up to set email alerts
|

GATA1 Is a Sensitive and Specific Nuclear Marker for Erythroid and Megakaryocytic Lineages

Abstract: Objectives: GATA binding factor 1 (GATA1) is a transcription factor essential for erythromegakaryocytic differentiation. Given its function in lineage specification, we sought to evaluate the immunohistochemical profile of GATA1 in normal marrow and acute leukemia and assess the use of GATA1 as a specific erythromegakaryocytic immunohistochemical marker. Methods:Immunohistochemical studies for GATA1 expression were performed on bone marrow biopsy specimens to define its role in the evaluation of acute leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…We wanted to confirm the relevance of these findings at the single cell level in hematopoietic progenitors in vivo in DBA patients. As primary patient samples are often limited and challenging to obtain, we developed a semi-quantitative immunohistochemistry staining method for GATA1 protein expression (Lee et al, 2017). We could individually identify and measure the staining intensity of GATA1 in the nuclei of erythroid precursors and progenitors from bone marrow biopsies obtained from healthy controls or from DBA patients (Carpenter et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We wanted to confirm the relevance of these findings at the single cell level in hematopoietic progenitors in vivo in DBA patients. As primary patient samples are often limited and challenging to obtain, we developed a semi-quantitative immunohistochemistry staining method for GATA1 protein expression (Lee et al, 2017). We could individually identify and measure the staining intensity of GATA1 in the nuclei of erythroid precursors and progenitors from bone marrow biopsies obtained from healthy controls or from DBA patients (Carpenter et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…For each of seven different DBA patients and three normal healthy controls, bone marrow biopsy sections were immunohistochemically stained for GATA1, as previously described (Lee et al, 2017). All sections were stained and imaged together to ensure consistency between samples.…”
Section: Methodsmentioning
confidence: 99%
“…We first examined the expression of HSP60 in wildtype yolk sac erythrocytes at E9.0 using immunofluorescence staining. The erythrocytes were labeled with GATA1, a transcription factor which has been shown to play an essential role in erythromegakaryocytic differentiation and has been widely used as a sensitive and specific marker for erythroid and megakaryocytic lineages 20,21 . The voltage-dependent anion channel (VDAC) and Cytochrome C (Cyt C) are two mitochondrial proteins commonly used to label the distribution of mitochondria inside cells 22,23 .…”
Section: Resultsmentioning
confidence: 99%
“…GATA1 is related to the ampli cation of chromosome 21, even if it is found in non-DS-AMKL [7,17,22,23].GATA1 encodes a zinc-nger transcription factor that regulates the normal development of the erythroid, megakaryocytic, and basophilic/mast cell lineages, and is associated with transient myelopoiesis and DS-AMKL [24][25][26]. A recent study showed that GATA1 mutations can be detected in 11% of non-DS-AMKL patients and that lowintensity chemotherapy may also be effective in these patients [27,28].…”
Section: Discussionmentioning
confidence: 99%